Le De disciplinis de Jean-Louis Vivès : critique et rémanence du principe d’autorité - Vigliano, Tristan (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2011)
During the 1520s and 1530s, humanism continued to define itself with regards to research, re-discovery, edition, and commentary of ancient texts. However, it also entered a more critical phase, one that is more reflective, or conscious of its own existence. The De disciplinis appeared at Antwerp in July 1531, published by Michaël Hillen. Contrary to the traditional compendium of “authority,” Vivès affirms that it would be better to form an opinion on the writing of great authors according to what you have read, than to depend only on their expertise and to always accept the words of others. Secondhand knowledge is secondrate. Yet, not all authority is criticized in the same manner; there are both great and inferior authors, and it is important to consider their hierarchy. This article studies in depth the system of references and readings in the De disciplinis, in the context of the development of humanism and the calling into question of traditions surrounding the concept of “authority.” The paradox facing the critical undertaking would then be the danger of becoming itself a discourse of authority.